The Evaluation of Rural Budget Alocation Efectivity to Motoling Timur District Minahasa Selatan Regency - Boki, Cerri; Kiyai, Burhanuddin; Ruru, Joorie Marhaen (Sam Ratulangi University, 2015)
ABSTRACTAllocation of funds village is part of the balance funds received district / city, village fund allocation of at least 10% of the balance funds received by the district / city in the budget revenue and expenditure net of fund special allocation. The purpose of the Village Fund Allocation (ADD) is to Improve the organization of village government in carrying out government services and community development in accordance with its authority, Improve the ability of an association of villages and village in the planning, implementation and control of participatory development in accordance with the potential of the village, improving income distribution , employment and business opportunities for rural and urban communities, non-governmental Encourage increased mutual aid society.The purpose of this study was to evaluate the extent of the effectiveness of the allocation of funds in the village of East Motoling District of South Minahasa District. Data collection techniques in this research is through: Observation of the direct observation to the study site, melakukakan Interviews and Documentation.The evaluation result shows that the allocation of funds village in the district East Motoling not effective because there are still some things that are not appropriate as the manufacture of the plan to use the village fund allocation that does not involve people who mislead people do not know exactly to what the actual village fund allocation. Likewise, there is a budget that is used only for personal and group interests such as technical guidance old law that has all the roads when it would be better if the allocation of the funds are used for community development. In addition, the supervision of the district governments are still lacking that causes the allocation of village funds are not utilized properly.Keywords: Evaluation of Effectiveness of the Village Fund Allocation